The Populist Identity of the Promoters of Alternative Medicine - Jakub K. Górka (Ksiegarnia Akademicka Publishing, 2021)
In this paper, the author compares phenomena of political populism and alternative medicine on the ground of – similar in structure and content – narrations (and identities created on their basis) of propagators and followers of these ideas/ social praxis. The main thesis of the paper is the assumption that the narrative and identity mechanisms of alternative medicine are analogous to those of political populism. The author tries to prove it in the context of their relation to their counterparts in the mainstream of power/knowledge, with the assumption that these are dialectical relations understood in a specific manner. The oppositions of populism–liberal democracy and alternative medicine–conventional medicine are real, but in the broader sense, they complement and need each other to preserve the cores of the system, which implicates ineffectiveness of those alternative discourses. This article presents examples of anti-elitism and conspiratorial thinking both in political populism and in alternative medicine. It turns out that populism and unconventional medicine are so closely connected that alternative medicine, in its attitudes, refers not only to medical statements, but also to political ones.